Assessing countermarks on a corroded silver Dachao Tongbao - Jankowski, L; Ward, S (Oriental Numismatic Society, 2016)
A temporary display devoted to Mongol coinage and entitled "Pax Mongolica (AD 1210-1350)" was recently organised at the Ashmolean Museum. The exhibition was an opportunity to display some rare and lesser known coins from the Islamic and East Asian collections. A rare and historically puzzling silver coin was therefore selected. The coin adopting the shape of Chinese coinage and bears the inscription 'dachao tongbao' ('Currency of the Great Dynasty') written using Chinese characters.